Strategi Komunikasi CSR Beasiswa Sobat Bumi dalam Pengelolaan Citra PT Pertamina (Persero) - Atifa Dinar Larasati; Diah Ayu Candraningrum (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The Sobat Bumi Scholarship Program is a Corporate Social Responsibility (CSR) initiative of PT Pertamina (Persero) that focuses on supporting education and strengthening sustainable values among university students. This study aims to analyze the implementation of CSR communication strategies within the program as an effort to manage the company’s image. The research employs a descriptive qualitative approach grounded in communication strategy concepts, CSR theory, and image management theory. Data were collected through in-depth interviews, documentation, and indirect observation, and were analyzed using NVivo 12 through data reduction, data display, and verification techniques. The findings indicate that the communication strategy is implemented through the integration of online and offline channels, including social media, digital publications, campus outreach, training programs, and alumni forums. This implementation contributes to strengthening stakeholder relationships and shaping a positive corporate image, aligned with the agenda and role of Government Public Relations in enhancing national public communication. However, communication effectiveness still faces challenges in message consistency and outreach to audiences with low exposure levels, requiring a more adaptive and participatory communication approach. Program Beasiswa Sobat Bumi merupakan inisiatif Corporate Social Responsibility (CSR) PT Pertamina (Persero) yang berfokus pada dukungan pendidikan dan penguatan nilai keberlanjutan bagi mahasiswa. Penelitian ini bertujuan menganalisis implementasi strategi komunikasi CSR dalam program tersebut sebagai upaya pengelolaan citra perusahaan. Penelitian menggunakan pendekatan kualitatif deskriptif dengan landasan konsep strategi komunikasi, CSR, dan teori manajemen citra. Data dikumpulkan melalui wawancara mendalam, dokumentasi, serta observasi tidak langsung, kemudian dianalisis menggunakan NVivo 12 dengan teknik reduksi, penyajian, dan verifikasi data. Hasil penelitian menunjukkan bahwa strategi komunikasi dijalankan melalui integrasi kanal daring dan luring, seperti media sosial, publikasi digital, sosialisasi kampus, pelatihan dan forum alumni. Implementasi tersebut berkontribusi dalam memperkuat hubungan dengan pemangku kepentingan dan membentuk citra positif perusahaan, yang selaras dengan agenda dan peran Public Relations Pemerintah dalam memperkuat komunikasi publik nasional. Namun, efektivitas komunikasi masih menghadapi kendala dalam konsistensi pesan dan jangkauan kepada publik dengan keterpaparan rendah, sehingga diperlukan pendekatan komunikasi yang lebih adaptif dan partisipatif.